2015
DOI: 10.1002/jbm.a.35425
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo study of hazardous effects of Ag nanoparticles and Arginine‐treated multi walled carbon nanotubes on blood cells: Application in hemodialysis membranes

Abstract: One of the novel applications of the nanostructures is the modification and development of membranes for hemocompatibility of hemodialysis. The toxicity and hemocompatibility of Ag nanoparticles and arginine-treated multiwalled carbon nanotubes (MWNT-Arg) and possibility of their application in membrane technology are investigated here. MWNT-Arg is prepared by amidation reactions, followed by characterization by FTIR spectroscopy, Raman spectroscopy, and thermogravimetric analysis. The results showed a good he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 71 publications
(153 reference statements)
2
19
0
Order By: Relevance
“…TGA (Fig. 2C) traces of the pristine and EG-treated GNP provide more evidence about functionalization by thermal analysis of samples [42]. While there is no significant weight loss in the trace of pristine GNP, a steady weight loss between 140 and 500°C is seen in the EG-treated GNP trace, confirming the decomposition of the functional groups.…”
Section: Functionalization Analysissupporting
confidence: 59%
“…TGA (Fig. 2C) traces of the pristine and EG-treated GNP provide more evidence about functionalization by thermal analysis of samples [42]. While there is no significant weight loss in the trace of pristine GNP, a steady weight loss between 140 and 500°C is seen in the EG-treated GNP trace, confirming the decomposition of the functional groups.…”
Section: Functionalization Analysissupporting
confidence: 59%
“…The peaks at 1415 cm −1 , 1424 cm −1 , 1681 cm −1 , and 1687 cm −1 correspond to the asymmetric and symmetric stretching vibrations of the -COO − group. This is consistent with previous reports [60,61]. These results indicated that ion pair complexes formed between alkalizers and the deprotonated carboxyl group in GA. wavenumber indicates that there is a hydrogen bond force between Kollidon ® VA64 and the alkalizers.…”
Section: Raman Spectroscopysupporting
confidence: 93%
“…The product was centrifuged at 5000 rpm for 20 min (Eppendorf Centrifuge, Eppendorf, Hamburg, Germany) and the precipitates washed with tetrahydrofuran (THF) at 5000 rpm for 20 min until the supernatant was crystal clear. The acylated carbon nanotubes (COCl-MWCNTs) were then dried in a vacuum oven at 70 °C for 24 h (Trade Raypa Espinar, Barcelona, Spain) [ 27 ].…”
Section: Methodsmentioning
confidence: 99%